Spatial distribution and migration law of respirable dust in fully mechanized mining face - Xiangjun CHEN; Xiangyang YE; Yibo LI; Peiqi ZUO (Meikuang Anquan)
For the problem that the dust sampling method can only measure the dust mass concentration at fixed working locations, and can not systematically reflect the spatial distribution characteristics and migration rules of the dust mass concentration in the working face, taking the N1219 fully mechanized mining face of Ningtiaota Coal Mine as the research object, a three-dimensional numerical simulation was conducted on the spatial distribution and transport law of respirable dust (hereinafter referred to as “exhaled dust”) in the fully mechanized mining face using Fluent software, using the method of bidirectional coupling between discrete and continuous phases. The simulation results show that the particle size of dust particles on the side of the shearer is generally higher than that on the side of the hydraulic support. Considering that there is air leakage when the air flow on the support side flows towards the goaf, the carrying capacity of the air flow is weakened, and the particle size of dust particles carried is smaller; the dust generated by drum coal cutting presents two stages in the direction of the working face: the section between 70 m and 120 m from the intake airway is a “rapid descent section”, and the section between 120 m and 280 m from the intake airway is a “slow descent section”. In addition, the maximum mass concentration of dust generated in the direction of the working face can reach 1 600 mg/m3; in the inclined direction of the working face, the farther away from the coal wall, the lower the dust mass concentration generated by the drum cutting coal, and the dust mass concentration decreases to 0 mg/m3 at a distance of 4-5 m from the coal wall; in the section from 80 m to 280 m, all the dust generated by moving the frame is concentrated on the side of the hydraulic support; in the range of 40 m to 240 m, the mass concentration of exhaled dust carried by ventilation is evenly distributed in the height direction of the working face.